PERANCANGAN TATA LETAK GUDANG GULA PASIR PABRIK GULA (PG) GONDANG BARU KLATEN - , FAJAR SEPTI RAHAYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Granulated sugar is one important commodity for the community. As a commodity, the availability of refined sugar should be maintained to meet the needs of the national sugar. The importance of designing the layout of a warehouse for the storage of sugar is good and minimizing biayapemindahan materials. Indonesia has had the Indonesian National Standard (SNI), which is sni 7331:2007 warehouse regarding the provision of agricultural commodity warehouse and can be used as a guide to the layout of the sugar mill Sugar Factory Gondang Baru. This study begins to define the SNI 7331:2007 standard provisions regarding agricultural commodity barn. The study was conducted by looking at the condition of the existing warehouse, and an evaluation of the SNI. The design layout is done with a sugar warehouse scenario 1 and scenario 2 using the palette using bamboo. Final stages of analyzing the best foundation to use the warehouse on the current conditions. The results of this study indicate there is a 9% SNI requirements are not appropriate and necessary proposals perbaikan.Tata warehouse layout is best layout with bamboo base, five key heap, pile up to a maximum of 40 piles, divided 4 staple andcan accommodate 114 400 sacks.